2016
DOI: 10.18632/oncotarget.13617
|View full text |Cite
|
Sign up to set email alerts
|

Has aidi injection the attenuation and synergistic efficacy to gemcitabine and cisplatin in non-small cell lung cancer? A meta-analysis of 36 randomized controlled trials

Abstract: Gemcitabine and cisplatin is the first line chemotherapy for non-small cell lung cancer with high toxicity. Aidi injection is a cantharidin and astragalu-based Chinese herbs injection in China. Has Aidi injection attenuation and synergistic efficacy to GP in NSCLC? There is lack of strong evidence to prove it. To further reveal it, we systematically evaluated all related studies. We collected all studies about Aidi injection plus GP for NSCLC in Medline, Embase, Web of Science, CNKI, VIP, Wanfang Database, CBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Compared to the previous studies [14, 31], this meta-analysis revealed that Aidi injection plus docetaxel-based chemotherapy, especially plus DP, DC, and DO, might significantly improve the ORR and DCR and 50 ml was the main dosage. Our previous meta-analysis [67, 68] had shown that Aidi injection plus radiotherapy or gemcitabine and cisplatin (GP) could significantly improve the QOL in patients with lung cancer. Can Aidi injection plus docetaxel-based chemotherapy improve the QOL?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the previous studies [14, 31], this meta-analysis revealed that Aidi injection plus docetaxel-based chemotherapy, especially plus DP, DC, and DO, might significantly improve the ORR and DCR and 50 ml was the main dosage. Our previous meta-analysis [67, 68] had shown that Aidi injection plus radiotherapy or gemcitabine and cisplatin (GP) could significantly improve the QOL in patients with lung cancer. Can Aidi injection plus docetaxel-based chemotherapy improve the QOL?…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that it also had low risk of anemia, hepatorenal dysfunctions, and alopecia. Our previous study [67] had shown that Aidi injection plus GP had low risk of hematological and gastrointestinal toxicity and neurotoxicity in NSCLC. Furthermore, Aidi injection could alleviate the radiotherapy related toxicity, such as myelosuppression, radiation pneumonitis, and esophagitis [68].…”
Section: Discussionmentioning
confidence: 99%
“…A related meta‐analysis has shown that sodium cantharidinate and vitamin B6 could improve the clinical response and QOL in patients with intermediate or advanced hepatocarcinoma. Another meta‐ananlysis has shown that cantharis and astragalus‐based Chinese Herbs injection (Aidi injection) showed synergistic efficacy to chemotherapy or radiotherapy in lung cancer. Animal studies have shown that cantharidin plus chemotherapy could significantly inhibit the growth of Lewis lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we included 38 trials involving 2845 patients with NSCLC 62 Our previous studies 63 showed that Aidi injection plus gemcitabine and cisplatin had a low risk of haematotoxicity, neurotoxicity and nausea/vomiting in NSCLC. These studies provide indirect evidence supporting the conclusions in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It functions in particular with respect to the therapy of head and neck, testicular, small lung cell and ovarian cancers. [2][3][4][5] Unfortunately, cisplatin exhibits some drawbacks including severe side effects, 6 acquired drug resistance 7 and low water-solubility, 8 which seriously limit its clinical applications. To combat those limitations, researchers have been exploring new Ptcompounds to improve antitumor efficiency.…”
Section: Introductionmentioning
confidence: 99%